Language Learning Attitudes of Young Learners: Differences between Syrian Refugee Learners and Turkish Learners - Asmali, Mehmet; Sayın, Sanem Dilbaz (Acta Paedagogica Vilnensia, 2021)
Welcoming more than 1.7 million refugee and asylum-seeker children, Turkey has put a considerable effort in turning this tragedy into an advantage for these children in terms of their education. Language teaching has played a remarkable role in this effort. Turkey has offered both Turkish and English language courses to these people. Considering the significance of English as a global language for social integration and future studies, this study attempted to investigate young Syrian refugee students’ attitudes toward English language and their reasons to learn English. Moreover, their perspectives were compared with Turkish young learners. Thirty-eight Turkish and 26 Syrian 5th graders (aged 10–11) voluntarily participated in this study. The findings indicated that learning English makes Syrian students happy, whereas Turkish students enjoy the fun activities in English classes. Learning English is considered both relatively easy and important by both groups. Turkish and Syrian young learners’ reasons to learn English differed slightly. Suggestions were provided for refugee young learners to overcome the potential problems regarding language learning.